2021
DOI: 10.3390/ma14020345
|View full text |Cite
|
Sign up to set email alerts
|

Use of Steel Slag as an Alternative to Aggregate and Filler in Road Pavements

Abstract: Today the use of Construction and Demolition Materials (CDM) can be considered as a suitable solution for the construction or the rehabilitation of road pavements. In this context, it is central to minimizing waste production, favoring the reuse through new production cycles to replace virgin natural raw materials. As illustrated in this study, steel slag has mechanical properties that justify its use as aggregate in the manufacture of bituminous mixes. In road construction, their use is focused on the substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Selected studies [12][13][14][15][16][17][18][19][20][21] of numerous recent research works reported to the scientific journal Materials were devoted to the use and incorporation of steel slags in road construction materials and concrete. The BOF slag incorporated in the asphalt mixture is advantageous for improving the ability of this mixed material to resist the deformation and enhancing the stability of structure, according to Ye et al [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selected studies [12][13][14][15][16][17][18][19][20][21] of numerous recent research works reported to the scientific journal Materials were devoted to the use and incorporation of steel slags in road construction materials and concrete. The BOF slag incorporated in the asphalt mixture is advantageous for improving the ability of this mixed material to resist the deformation and enhancing the stability of structure, according to Ye et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…Skaf et al [13] produced a porous asphalt mixture with 100% EAF slag aggregates that met the current standards for sustainable and environmentally friendly mixtures. Dondi et al [15] stated that the asphalt mixture containing 30 % of steel slag is characterized by high stability and stiffness. Liu et al [14] suggested that pits and grooves on the surface of steel-slag particles provided a skeleton-like function for the bitumen-steel slag aggregate interface improving the adhesion strength of the bitumen-steel slag aggregate interface.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter scenario, the ingredients become part of the slags, which can be then used in civil engineering or road construction. [ 63 ] The same applies to interconnect coatings and the oxide scales, which are both irrelevant for SOC‐recycling.…”
Section: Future Recycling Of Socsmentioning
confidence: 99%
“…Asphalt binder can be modified with different materials such as polymers, jet grouting waste, steel slag, and recycled asphalt to achieve desired properties [1][2][3][4][5]. Asphalt binder is the residue of crude petroleum with properties depending on its source and refining process [6].…”
Section: Introductionmentioning
confidence: 99%